Academy of Dental Materials guidance—Resin composites: Part II—Technique sensitivity (handling, polymerization, dimensional changes). Issue 11 (November 2017) - Ferracane, J.L.; Hilton, T.J.; Stansbury, J.W.; Watts, D.C.; Silikas, N.; Ilie, N.; Heintze, S.; Cadenaro, M.; Hickel, R.
Abstract: Objective: The objective of this work, commissioned by the Academy of Dental Materials, was to review and critically appraise test methods to characterize properties related to critical issues for dental resin composites, including technique sensitivity and handling, polymerization, and dimensional stability, in order to provide specific guidance to investigators planning studies of these properties. Methods: The properties that relate to each of the main clinical issues identified were ranked in terms of their priority for testing, and the specific test methods within each property were ranked. An attempt was made to focus on the tests and methods likely to be the most useful, applicable, and supported by the literature, and where possible, those showing a correlation with clinical outcomes. Certain methods are only briefly mentioned to be all-inclusive. When a standard test method exists, whether from dentistry or another field, this test has been identified. Specific examples from the literature are included for each test method. Results: The properties for evaluating resin composites were ranked in the priority of measurement as follows: (1) porosity, radiopacity, sensitivity to ambient light, degree of conversion, polymerization kinetics, depth of cure, polymerization shrinkage and rate, polymerization stress, and hygroscopic expansion; (2) stickiness, slump resistance, and viscosity; and (3) thermal expansion. Significance: The following guidance is meant to aid the researcher in choosing the most appropriate test methods when planning studies designed to assess certain key properties and characteristics of dental resin composites, specifically technique sensitivity and handling during placement, polymerization, and dimensional stability.